Rapid and sensitive detection of botulinum toxin type A in complex sample matrices by AlphaLISA - Liwen Zhang; Liwen Zhang; Qingyu Lv; Yuling Zheng; Shan Gao; Wenhua Huang; Peng Liu; Decong Kong; Ye Wang; Yunzhou Yu; Yongqiang Jiang; Yongqiang Jiang; et al. (Frontiers in Public Health, 2022)
Botulinum toxin A(BoNT/A) is a neurotoxin produced by the bacteria Clostridium botulinum, which can cause serious food poisoning and is recognized as a potential biological warfare agent. BoNT/A is does not degrade easily and can remain in the complex matrix for a long time. Meanwhile, the poisonous dose of botulinum toxin exceptionally low and intravenous human lethal doses estimated at 1-3 ng/kg. Therefore, sensitive and accurate detection methods suitable for testing a wide range of complex samples are urgently needed. To this end, the “amplified luminescent proximity homogeneous assay linked immunosorbent assay” (AlphaLISA) was established for the detection of BoNT/A and its detection efficacy in plasma, beverage, food, and other complex samples was evaluated. The results showed that this method can very effectively resist matrix interference. The detection time is rapid, reaching a detection limit for all samples of up to 0.1 ng/mL in only 30 min. BoNT/A can also be accurately detected in vomit samples of patients with clinical food poisoning. This study demonstrates that AlphaLISA is an effective tool for the detection of BoNT/A in complex samples and can potentially be developed for commercial use in the future.